Archaeological Heritage in a Modern Urban Landscape: The Ancient Moche in Trujillo, Peru - Gamboa Velásquez, Jorge (Springer, 2015)
Archaeological Heritage in a Modern Urban Landscape evaluates issues about the preservation, social role and management of archaeological sites in the Trujillo area, north coast of Peru, specifically those of the Moche culture (100-800 AD). Moche was one of the great civilizations of ancient Peru, with spectacular ceremonial adobe architecture and settlements distributed across a landscape formed by coastal valleys and one of the largest deserts of South America. In the last decades political and economic changes have brought rural migrations to the city of Trujillo and nearby zones, causing the emergence of extensive new communities in the margins of the metropolis. And although Trujillo’s Moche heritage has become a symbol of regional identity, most local Moche sites are under siege because of urban development. This book offers a new perspective on the development of modern communities settled beside archaeological sites and contributes to improving best practices in the management of archaeological sites and preservation in an urban setting.